2002
DOI: 10.1046/j.1365-2427.2003.00967.x
|View full text |Cite
|
Sign up to set email alerts
|

Life history and reproductive capacity of Gammarus fossarum and G. roeseli (Crustacea: Amphipoda) under naturally fluctuating water temperatures: a simulation study

Abstract: SUMMARY 1. Mathematical functions developed in long‐term laboratory experiments at different constant temperatures were combined with daily water temperatures for 1991–93 in eight Austrian streams and rivers to simulate the complex life histories and reproductive capacities of two freshwater amphipods: Gammarus fossarum and G. roeseli. The functions describe brood development times, hatching success, times taken to reach sexual maturity, growth, and fecundity. The sex ratio was assumed to be 0.5 and an autumn–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
65
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 32 publications
5
65
3
Order By: Relevance
“…The lowest number of ovigerous females for G. roeselii was recorded during October. Similar studies reveal a reduced reproduction during autumn (Pöckl et al, 2003). In this study, the presence of ovigerous females has been recorded throughout the year in the other two species as well.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The lowest number of ovigerous females for G. roeselii was recorded during October. Similar studies reveal a reduced reproduction during autumn (Pöckl et al, 2003). In this study, the presence of ovigerous females has been recorded throughout the year in the other two species as well.…”
Section: Discussionsupporting
confidence: 87%
“…Similar studies have shown that Gammarus roeselii is more successful in maintaining viable and highly productive populations in waters originating from thermal springs (Pöckl et al, 2003) During this investigation we have found a continuous reproduction cycle of G. roeselii throughout the year. Previous studies of G. fossarum and G. roeselii had shown that higher temperatures are generally associated with shorter life spans, faster brood development times, a tendency to produce more broods, and greater reproductive potential capacity in terms of succeeding generations (Pöckl et al, 2003). The lowest number of ovigerous females for G. roeselii was recorded during October.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Increases in annual mean water temperature values of around 1.5°C, and changes in summer mean river temperatures of more than 2°C, would have had an impact on the thermal habitats of freshwater faunas (cf. Pöckl et al, 2003). The effects of flow changes on river temperatures are less clear cut.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these studies must be developed in different habitats with particular characteristics, such as temporary streams, saline streams, streams with constant temperature, etc., in order to characterize the key factors that influence the life history of the organisms in a given environment. The species Gammarus fossarum (Koch, 1836) is the most frequent species of gammarids in freshwater stream of mountainous areas of central Europe (Pöckl et al 2003) and plays a major role in the breakdown of leaf litter. Because G. fossarum is so widespread, frequently abundant, an important and obvious member of most freshwater communities, it has been extensively studied from a variety of viewpoints.…”
Section: Introductionmentioning
confidence: 99%